2017
DOI: 10.1002/jmv.24859
|View full text |Cite
|
Sign up to set email alerts
|

Impact of “a” determinant mutations on detection of hepatitis B surface antigen (HBsAg) in HBV strains from Chinese patients with occult hepatitis B

Abstract: This study was designed to detect mutations that occur within the "a" determinant in the S gene of the hepatitis B virus (HBV) in patients with occult hepatitis B (OHB), and to analyze the influence of these mutations on expression and reactivity of the hepatitis B surface antigen (HBsAg). Twenty-three certified OHB samples were compared to 32 HBsAg positive samples from patients with chronic hepatitis B. The median HBV DNA levels in the OHB group were significantly lower than those in the control group (P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
2
5
1
Order By: Relevance
“…In the present study, there was no significant difference between HBsAgNx-negative and HBsAgNx-positive NAT yield or OBI groups in the frequency of samples with substitutions or in the average number of substitutions per sample for the PreS1, PreS2, or S regions (Table 1). In contrast, there were significantly more S substitutions in the OBI samples than in the comparison HSLD group in which HBsAg was readily detectable (Tables 1 and 6), a finding similar to other reports on the increased frequency of MHR substitutions in OBI [16,[22][23][24][25]. HBsAg substitutions, particularly in the 'a' determinant within the MHR, have been associated with the lack of detection by affecting antigen binding to antibodies used in HBsAg immunoassays [16].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the present study, there was no significant difference between HBsAgNx-negative and HBsAgNx-positive NAT yield or OBI groups in the frequency of samples with substitutions or in the average number of substitutions per sample for the PreS1, PreS2, or S regions (Table 1). In contrast, there were significantly more S substitutions in the OBI samples than in the comparison HSLD group in which HBsAg was readily detectable (Tables 1 and 6), a finding similar to other reports on the increased frequency of MHR substitutions in OBI [16,[22][23][24][25]. HBsAg substitutions, particularly in the 'a' determinant within the MHR, have been associated with the lack of detection by affecting antigen binding to antibodies used in HBsAg immunoassays [16].…”
Section: Discussionsupporting
confidence: 86%
“…Thus, the observed HBsAgNx-negative results were likely due to very low levels of virus rather than assay failure. A similar conclusion was reported in a study comparing the HBsAg detection of six native samples carrying ten 'a' determinant mutations with recombinant proteins derived from the native samples [25]. Although the native samples were HBsAg-negative by sensitive immunoassays, all ten of the recombinant proteins were detected.…”
Section: Discussionsupporting
confidence: 83%
“…Studies have shown that some patients with OBI harbour a higher proportion of mutations in the preS/S region than patients with CHB, which may result in a reduced antigenicity for HBsAg detection or impairment in HBsAg production or secretion. 7,12,[36][37][38][39][40][41] The mutations in pre-S1 may also alter the B and T epitopes that affect immune recognition. 7 However, HBV DNA isolated from individuals with OBI is fully replication competent in vitro, 42 and the virus can also be transmitted via blood transfusion or organ transplantation.…”
Section: Virology Epigenetics and Immunology Of Obimentioning
confidence: 99%
“…The ‘a’ determinant within the major hydrophilic loop of the S protein contains viral epitopes which are not only targets for neutralizing antibody responses in natural infection and vaccine recipients but also the region detected in most detection assays 34,35 . Hence amino acid substitutions in this region often result in immune escapes mutants, vaccine failures and also evade detection, technically resulting in OBI 17,34,36 . We found mutant T528C (Met125Thr) within this region in all ten of our patients analyzed which may explain HBsAg negativity accounting for OBI.…”
Section: Discussionmentioning
confidence: 99%